Peran Pembimbing Kemasyarakatan dalam Pembimbing dan Pengawasan Klien Selama Menjadi Masa Integrasi di BAPAS Kelas 1 Palembang - Putri, Ida Lestari; Kusnadi, Kusnadi; Noviza, Neni (Journal of Society Counseling, 2023)
This research is entitled "The Role of Community Counselors in Guiding and Supervising Clients During the Integration Period at Bapas Class 1 Palembang". This research aims to determine the role of community counselors and the obstacles faced by community counselors in guiding and supervising clients during the integration period at Bapas Class 1 Palembang. This research uses a qualitative descriptive research method. The subjects in this research were 2 community counselors at Bapas class 1 Palembang. The data collection techniques used were observation, interviews and documentation. Meanwhile, the data analysis techniques in this research are data reduction, presentation and drawing conclusions. The results of this research are the role of community counselors in guiding and supervising clients during the integration period at Bapas Class 1 Palembang, namely providing personality and independence guidance in the form of: strengthening client motivation, providing information, and providing opportunities to express feelings. Meanwhile, the obstacles faced by community counselors in guiding and supervising clients during the integration period: the father's location being different from the client, coordination facilities, provision of materials, and the client's lack of legal awareness. Efforts made by community counselors to reduce the obstacles faced include: community guidance via video call for clients who have a different location from Bapas, and advising clients to live in the same location as Bapas.